Developing an Effective Therapeutic HPV Vaccine to Eradicate Large Tumors by Genetically Fusing Xcl1 and Incorporating IL-9 as Molecular Adjuvants - Zhongjie Sun; Zhongyan Wu; Xuncheng Su (Vaccines)
Background: Human papillomavirus (HPV) is a prevalent infection affecting both men and women, leading to various cytological lesions. Therapeutic vaccines mount a HPV-specific CD8+ cytotoxic T lymphocyte response, thus clearing HPV-infected cells. However, no therapeutic vaccines targeting HPV are currently approved for clinical treatment due to limited efficacy. Our goal is to develop a vaccine that can effectively eliminate tumors caused by HPV. Methods: We genetically fused the chemokine XCL1 with the E6 and E7 proteins of HPV16 to target cDC1 and enhance the vaccine-induced cytotoxic T cell response, ultimately developing a DNA vaccine. Additionally, we screened various interleukins and identified IL-9 as an effective molecular adjuvant for our DNA vaccine. Results: The fusion of Xcl1 significantly improved the quantity and quality of the specific CD8+ T cells. The fusion of Xcl1 also increased immune cell infiltration into the tumor microenvironment. The inclusion of IL-9 significantly elevated the vaccine-induced specific T cell response and enhanced anti-tumor efficacy. IL-9 promotes the formation of central memory T cells. Conclusions: the fusion of Xcl1 and the use of IL-9 as a molecular adjuvant represent promising strategies for vaccine development.